Letter from Max Bredig to Fridel G. Halstead, December 21, 1938 - Bredig, Max Albert (1938)
Max Bredig (1902-1977) informs Fridel G. Halstead that he will be writing affidavits for his sister, Marianne Homburger (1903-1986), his brother-in-law, Viktor Homburger (1888-1968), and his father, Georg Bredig (1902-1944).
Keywords: Bredig, Max Albert, 1902-1977; Halstead, Fridel G.; Bredig, Georg, 1868-1944; Homburger, Marianne, 1903-1986; Homburger, Viktor, 1888-1968; Affidavits